ANALISIS KEMAMPUAN SISWA SMP MENJELASKAN KONSEP IPA DENGAN VARIASI MEDIA PEMBELAJARAN VISUAL - Adi Nugraha, Andhika; Susiyawati, Enny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ ability to explain science concepts is one of the key indicators of conceptual understanding. However, this ability remains relatively low, particularly when dealing with abstract material. One factor believed to influence this ability is the use of visual learning media with different characteristics. This study aims to determine the ability of junior high school students and the differences in their ability to explain science concepts through various visual learning media, namely instructional videos, three-dimensional (3D) models, and two-dimensional (2D) images. The study was conducted at SMP Negeri 18 Surabaya during the even semester of the 2025/2026 academic year with 30 seventh-grade students as research subjects. Data were collected through explanation ability tests, interviews, and student response questionnaires. The research instruments included essay questions, interview guidelines, and a Likert scale questionnaire. The results showed that instructional videos yielded the highest average explanation ability score of 75.25, followed by 3D models at 74.33, and 2D images at 71.33. Each medium demonstrated strengths in different indicators of explanatory ability according to its characteristics. Interview and questionnaire data also showed that all three media received positive responses from students, although each had its own strengths and limitations in supporting conceptual understanding. It was concluded that variations in visual learning media result in different tendencies in explanatory ability depending on the characteristics of the information presented. Teachers are advised to combine the use of these three types of visual learning media because each medium has distinct characteristics, indicator focuses, and roles in enhancing explanatory ability; thus, each medium can complement the students’ ability to explain science concepts.